Diretoria de Serviço de Atividades Auxiliares e Seção de Atividades Auxiliares - Souza, Paulo Henrique de; Storti, Carlos Eduardo; Gomes, Marco Antônio; Pereira, Alexandrina Maria; Souza, Antonio Ferreira de; Carvalho, Aparecida Fátima Christófano de; Carvalho, Aparecida Leontina Baiochi de; Oliveira, Ednir José Barbosa de; Souza, Edson Almeida de; Eugenio, Fatima Aparecida Vieira; Dourado, Grazielle Lourenço; Ribeiro, Ivanilde da Silva; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Paulo Henrique de Souza